ANGPTL4 Attenuates Ang II-Induced Atrial Fibrillation and Fibrosis in Mice via PPAR Pathway - Xi Zhu; Xiaogang Zhang; Xinpeng Cong; Luoning Zhu; Zhongping Ning (Cardiology Research and Practice)
Atrial fibrillation (AF) is the more significant portion of arrhythmia in clinical practice, with inflammation and fibrosis as its central pathological mechanisms. This study aimed to investigate angiopoietin-like 4 (ANGPTL4) effects on angiotensin II- (Ang II-) induced AF and its related pathophysiological mechanisms. C57BL/6J mice were randomized and divided into three groups: the control group, the Ang II group, and the ANGPTL4 group (Ang II with ANGPTL4 treatment). Mice were infused with Ang II (2000 ng/kg/min) and were administrated with recombinant human ANGPTL4 (rhANGPTL4, 20 μg/kg/day) for 3 weeks. The fibrosis was evaluated with Masson’s trichrome staining in the atrial myocardium. mRNA levels of IL-1β, IL-6, collagen I, and collagen III were measured using real-time qRT-PCR. Protein levels of PPARα, PPARγ, CPT-1, and SIRT3 were measured using Western blotting. Compared to the control group, the mice infused with Ang II showed electrocardiogram characteristics of AF, and this effect was markedly attenuated in ANGPTL4-treated mice. ANGPTL4 also reversed the increase in cardiomyocyte apoptosis, inflammation, interstitial collagen fraction, and collagen gene expression in mice with Ang II. Mechanistically, ANGPTL4 inhibited the activation of several fatty acid metabolism-related proteins, including PPARα, PPARγ, and CPT-1, and the expression of SIRT3 protein in atrial tissues. In conclusion, ANGPTL4 attenuates Ang II-induced AF and atrial fibrosis by modulation in the SIRT3, PPARα, and PPARγ signaling pathways.